The impact of organizational factors towards the information system success among KPDNKK Batu Pahat / Muhd Shah Hazwan Jamaluddin , Siti Rosnani Mokri and Wan Amalina Wan Anuar - Jamaluddin, Muhd Shah Hazwan; Mokri, Siti Rosnani; Wan Anuar, Wan Amalina (Faculty of Business and Management, 2012)
This study attempted to examine the impact of organizational factor towards the information system success among KPDNKK Batu Pahat employees. The objectives of conducting this research are to identify the level of E-aduan system success at Kementerian Perdagangan Dalam Negeri, Koperasian dan Kepenggunaan (KPDNKK) Batu Pahat and also to identify the relationship between the organizational factors and E-aduan system success at KPDNKK Batu Pahat. A questionnaire was used as the main instrument for the purposed of data collection. This questionnaire consists of eight different sections; system quality, perceived usefulness, user satisfaction, information quality, top management support, goal alignment, resource allocations, and demographic information. The items in the questionnaire were constructed according to research objectives and research questions. The respondents of this research consist of employees from KPDNKK Batu Pahat. The data analyzed using the SPSS version 20.0. As a conclusion, this study will help the organization to improve their productivity by embracing the concept and implementation of the technology welcoming the educational and administrative benefits that it has to offer. Other than that, this study will help the employees within the organization to understand better of the importance of adopting the e-Aduan system, which could help to boost their work performance and increase their productivity. Researchers suggested that the organization must upgrade the content or software that is used in the system to make the employees feel more satisfied and this will contribute to the possibility of them to log in into this system as one of the medium for performing their task.